Polska krytyka filmowa kina dokumentalnego w czasopismach branżowych. Od końca II wojny światowej do przełomu cyfrowego. Rekonesans badawczy - Drewniak, Mateusz (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2025)
The subject of this paper is Polish film criticism of documentary cinema present in the Polish trade magazines from the end of the Second World War (1945) to the digital turn (circa 2000). The starting point for undertaking this topic was two library searches at the Library of the Polish National Film Archive in Warsaw. As a result, the author compiled an atlas of critical texts on film (which were created in the indicated time period and published in the selected trade magazines), presented their genological division and pointed out the most important places of their publication. Then looking at this map, he highlighted several names of publicists, some of which caught his special attention. The final aim of this analysis involves the wish to inspire other researchers to show interest in the topic indicated above. The atlas offered in this work is intended to serve film, cultural and media scholars as an inspiration to undertake further research on documentary cinema journalism in Poland.